2019
DOI: 10.1039/c8tc05489d
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired electronic synapse using solution processable organic small molecule

Abstract: A trap-mediated solution-processed small molecule based artificial synaptic device is presented. This work reveals great potential for a small molecule based artificial synapse to serve in neuromorphic computing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 54 publications
3
37
0
Order By: Relevance
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…Mao et al recently reported a memory device based on an active material of (bis‐4‐[ N ‐carbazolyl]phenyl)phenylphosphine oxide (BCPO, Figure 6C). 99 The ITO/BCPO/Al device presented high reproducibility, excellent endurance, good thermal stability, and biological synapse mimic ability. Moreover, four‐level distinct resistive states were successfully obtained by gradient adjustment of the CCs from 10 −4 to 10 −1 A (ie, 10 −4 , 10 −3 , 10 −2 , and 10 −1 A, Figure 6D), indicating potential application for multilevel information storage.…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%
“…Hardware implementation aims to construct artificial neurons networks by using electronic devices. Since synapses are the functional connections of neurons and serve as the basic units of computing and learning, designing physical synaptic devices that exhibit synaptic behaviors is the key step to build brain‐like computers . In the past few decades, silicon‐based complementary metal‐oxide semiconductor (CMOS) analogue circuits have been proposed to simulate the synaptic functions .…”
Section: Introductionmentioning
confidence: 99%
“…It also enables efficient photoinduced charge transfer, charge separation and bipolar charge transport materials for light‐emitting diodes, lasers and other applications . Molecules comprising of electron donor (D) unit and an electron acceptor (A) unit have been recognized as high‐performance materials in optoelectronic applications, such as organic light emitting diodes (OLED), organic solar cells (OSC) and organic photovoltaics (OPV) …”
Section: Introductionmentioning
confidence: 99%